2024
DOI: 10.1021/acsmaterialslett.3c01533
|View full text |Cite
|
Sign up to set email alerts
|

Activatable Plasmonic Versatile Nanoplatform for Glutathione-Depletion Augmented Ferroptosis and NIR-II Photothermal Synergistic Therapy

Tao Sun,
Liang Zhang,
Shilin Xiao
et al.

Abstract: Ferroptosis-based therapy exhibits promising prospects for the treatment of malignant tumors. However, the practical therapeutic benefits of ferroptosis-based antitumor therapy are usually restricted by excess endogenous antioxidants and relatively sluggish ROS production kinetics. Here, an activatable plasmonic versatile nanoplatform (AuSi@ FePB) with glutathione (GSH)-depletion capacity is reported for synergistic ferroptosis therapy and second near-infrared window photothermal therapy (NIR-II PTT). The nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Sun et al reported the development of the NIR-II activable nanoplatform termed AuSi@FePB, which was designed for synergistic ferroptosis therapy and photothermal therapy. 76 The fabrication of the AuSi@FePB nanoplatform involved coating a polydopamine shell coordinated with iron (Fe-PDA) on silica-encapsulated gold nanochains (AuNCs@SiO 2 ), with the GSH synthesis inhibitor l -BSO incorporated on the surface of Fe-PDA. NIR-II photoirradiation-induced local heating not only efficiently triggered photothermal therapy (PTT) but also notably amplified the Fenton reaction, resulting in the production of reactive oxygen species (ROS) and depletion of glutathione (GSH).…”
Section: Nir-responsive Nanomaterialsmentioning
confidence: 99%
“…Sun et al reported the development of the NIR-II activable nanoplatform termed AuSi@FePB, which was designed for synergistic ferroptosis therapy and photothermal therapy. 76 The fabrication of the AuSi@FePB nanoplatform involved coating a polydopamine shell coordinated with iron (Fe-PDA) on silica-encapsulated gold nanochains (AuNCs@SiO 2 ), with the GSH synthesis inhibitor l -BSO incorporated on the surface of Fe-PDA. NIR-II photoirradiation-induced local heating not only efficiently triggered photothermal therapy (PTT) but also notably amplified the Fenton reaction, resulting in the production of reactive oxygen species (ROS) and depletion of glutathione (GSH).…”
Section: Nir-responsive Nanomaterialsmentioning
confidence: 99%
“…In recent years, chemodynamic therapy (CDT) has emerged as a promising treatment modality. Fenton/Fenton-like reactions facilitate the conversion of H 2 O 2 into hydroxyl radicals, employing Fe and other metals with distinct valence states. When combined with photothermal therapy (PTT), this synergistic approach not only utilizes thermal energy to eradicate bacteria but also accelerates the generation of free radicals, thereby exhibiting synergistic antibacterial effects. , …”
Section: Introductionmentioning
confidence: 99%